2019
DOI: 10.1074/jbc.ra119.010130
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase δ inactivation prevents vitreous-induced activation of AKT/MDM2/p53 and migration of retinal pigment epithelial cells

Abstract: Edited by Xiao-Fan Wang Phosphoinositide 3-kinases (PI3Ks) are a family of lipid kinases that play a critical role in transmitting signals from cellsurface molecules to intracellular protein effectors. Key PI3Ks include PI3K␣, PI3K␤, and PI3K␦, which are regulated by receptors. The signaling pathway comprising the PI3Ks, along with a Ser/Thr kinase (AKT), a proto-oncogene product (mouse double minute (MDM)2), and a tumor suppressor protein (p53), plays an essential role in experimental proliferative vitreoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 74 publications
(105 reference statements)
0
15
0
Order By: Relevance
“…PDGF-BB has been reported to be capble to induce the underlying pathways of Erk, p38, JNK activation in PVR [37], on the other hand, TGFβ induces epithelial mesenchymal transition (EMT) [38,39] in RPEs. Thus, many signaling pathways are activated in PVR pathogenesis, of which especially Akt/MDM2/p53 among those signals is hyperactive in the virtreal environment [29,40]. Our data was clearly evident that CMR at 5 μM completely blocked vitreous-induced activation of Akt, and p53 attenuation, however, whether it can suppress the activation of Erk, p38 or JNK induced by vitreous remains unknown.…”
Section: Discussionmentioning
confidence: 61%
“…PDGF-BB has been reported to be capble to induce the underlying pathways of Erk, p38, JNK activation in PVR [37], on the other hand, TGFβ induces epithelial mesenchymal transition (EMT) [38,39] in RPEs. Thus, many signaling pathways are activated in PVR pathogenesis, of which especially Akt/MDM2/p53 among those signals is hyperactive in the virtreal environment [29,40]. Our data was clearly evident that CMR at 5 μM completely blocked vitreous-induced activation of Akt, and p53 attenuation, however, whether it can suppress the activation of Erk, p38 or JNK induced by vitreous remains unknown.…”
Section: Discussionmentioning
confidence: 61%
“…38 Idelalisib at 1 μmol/L completely inhibited vitreous-induced activation of Akt, but it did not block Erk activation at its 10 μmol/L concentration, 38 suggesting that idelalisib specifically blocked vitreous-stimulated activation of Akt. 38,39 Given that the formation of PVR is a complicated process, here we revealed for the first time that, as a natural compound, ). Therefore, we hypothesize that CMR can inhibit PVR, which is closely related to proliferation and migration of RPEs.…”
Section: Discussionmentioning
confidence: 69%
“… 38 Idelalisib at 1 μmol/L completely inhibited vitreous‐induced activation of Akt, but it did not block Erk activation at its 10 μmol/L concentration, 38 suggesting that idelalisib specifically blocked vitreous‐stimulated activation of Akt. 38 , 39 Given that the formation of PVR is a complicated process, here we revealed for the first time that, as a natural compound, CMR has the advantage of effective, multi‐target and low toxicity, in terms of blocking vitreous‐induced cellular responses contributes to PVR. CMR has been shown as a broad spectrum of biological activities, but there has not yet been any thorough investigation into the molecular mechanisms of CMR involved in different diseases except human reproductive system cancer.…”
Section: Discussionmentioning
confidence: 81%
“…However, the role of vitreous in the ocular pathology is still unclear. Based on our previous findings 7 we hypothesize the vitreous contains some soluble factors that can induce pathological angiogenesis from retina.…”
Section: Discussionmentioning
confidence: 83%
“…4 Recently, several papers have been published describing the angiogenic and inflammatory activity of vitreous obtained from proliferative diabetic retinopathy patients. 5 However, our previous findings showed that vitreous from healthy animals enhances the signaling pathway of phosphoinositide 3-kinase (PI3K)/Akt, cell proliferation and migration of human pigment retinal epithelial cells, 6,7 and the PI3K/Akt signaling pathway plays a critical role in angiogenesis. 8 In addition, tandem mass spectrometry showed that there are some pro-angiogenic proteins in the vitreous, and the majority of vitreal proteins detected are intracellular proteins, some of which may originate from retina.…”
Section: Introductionmentioning
confidence: 99%